Hubungan antara Persepsi terhadap Gaya Kepemimpinan Atasan dengan Kepuasan Kerja pada Pekerja Berpengetahuan - Muhammad Nuradi Akhsan; Ali Nina Liche Seniati (Fakultas Psikologi Universitas Pancasila, 2009)
The focus of the study is the relationship between Bass's (1985) transformational and transactional leadership style perceived by knowledge worker with Spector's (1997) job satisfaction on knowledge worker. The present study is a correlational field study. The purpose of this study is to give additional evidence on which leadership style predicts higher job satisfaction. According to this research, group of knowledge worker who work under transformational leader achieve higher job satisfaction than those who work under transactional leader.